Inseguridad alimentaria, hábitos alimentarios y estado nutricional en hogares del distrito de San Juan Bautista en tiempos de pandemia, 2022 - Hidalgo Sáenz, Ambar (2023)
With the perspective that the authorities take into account studies being conducted in the Loreto Region, this research aimed to identify food insecurity, food habits and nutritional status in households in four rural and urban human settlements in the district of San Juan Bautista. The study was a non-experimental, descriptive correlational cross-sectional study, the study sample consisted of 184 households and 208 members of households in the human settlements of Las Amazonas, Bello Horizonte, Nuevo Amanecer and Ex petroleros in the district of San Juan Bautista. Direct interviews were used as a technique, the Experience-Based Food Insecurity Scale (FIES), a food consumption frequency questionnaire, and a nutritional assessment sheet were the instruments used to collect information. It was found that 100% of households in rural areas were severely food insecure, 43% were food insecure, 4.3% were mildly food insecure, and 2.7% were severely food insecure in urban areas. Likewise, 37.5% in rural areas had unhealthy eating habits, in urban areas 35.8% had healthy habits and 14.2% had unhealthy habits. For nutritional status, prevalence was found in both rural and urban areas of 45.2% and 53.3% in normal nutritional status and overweight. It is concluded that there is a relationship between eating habits, food insecurity and nutritional status.